Information Analytics for Healthcare Service Discovery. Issue 4 (16th December 2014) - Sun, Lily; Yamin, Mohammad; Mushi, Cleopa; Liu, Kecheng; Alsaigh, Mohammed; Chen, Fabian
Abstract : The concept of being 'patient-centric' is a challenge to many existing healthcare service provision practices. This paper focuses on the issue of referrals, where multiple stakeholders, such as General Practitioners (GPs) and patients, are encouraged to make a consensual decision based on patients' needs. In this paper, we present an ontology-enabled healthcare service provision, which facilitates both patients and GPs in jointly deciding upon the referral decision. In the healthcare service provision model, we define three types of profiles which represent different stakeholders' requirements. This model also comprises a set of healthcare service discovery processes: articulating a service need, matching the need with the healthcare service offerings, and deciding on a best-fit service for acceptance. As a result, the healthcare service provision can carry out coherent analysis using personalised information and iterative processes that deal with requirements which change over time.